5-aza-2'-deoxycytidine induces apoptosis and inhibits tumour growth in vivo of FaDu cells, a specific HPVnegative HNSCC cell line. - Reem Miari (Public Library of Science (PLoS), 2021)
Head and neck cancer squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide, resulting in over 600,000 new diagnoses annually. Traditionally, HNCC has been related to tobacco and alcohol exposure; however, over the past decade, a growing number of head and neck cancers are attributed to human papillomavirus (HPV) infection. 5-Aza-2'-deoxycytidine (5-AzaD) was demonstrated as an effective chemotherapeutic agent for acute myelogenous leukaemia. Preclinical data revealed that 5-aza inhibits growth and increases cell death of HPV(+) cancer cells. These effects are associated with reduced expression of HPV genes, stabilization of TP53, and activation of TP53-dependent apoptosis. The aim of the present study is to test the effect of 5-AzaD on growth of human squamous cell carcinoma (FaDu), a HPV(-) and p53 mutated cells, in vitro and in vivo. The effect of 5-AzaD on cell viability, cell cycle progression and induction of apoptosis was tested in vitro. The effect of 5-AzaD on tumour growth in vivo was tested using xenograft mice inoculated with FaDu cells. The results indicated that 5-AzaD reduced cell viability and induced apoptosis in FaDu cells in vitro. In vivo studies revealed that 5-AzaD suppresses the growth of tumours in xenograft mice inoculated with FaDu cells through inhibition of proliferation and induction of apoptosis. These findings may emphasis that 5-AzaD is effective in treatment of HPV(-) HNSCC tumours through TP53 independent pathway. Future studies are needed in order to clarify the molecular mechanism of action of 5-AzaD in HPV(-) cancer cells.